Effects of an Individual Work System on the Independent Functioning of Students with Autism - Hume, Kara; Odom, Sam (Journal of autism and developmental disorders, 2007)
This study examined the effects of a work system on the independent work and play skills of students with autism. Work systems, an element of structured teaching developed by Division TEACCH, are organized sets of visual information that inform a student about participation in work or play areas. A single subject withdrawal of treatment design, with replications across three participants, was used to assess the on-task behavior and work completion skills of the students in classroom and employment settings as a result of the intervention. Observational data indicated that all students showed increases in on-task behavior, increases in the number of tasks completed or play materials utilized, and reduction of teacher prompts. The results were maintained through the 1-month follow-up.